5PSQ-015 Comparing three criteria for assessment of what medicines included in national hospital formulary are classified as potentially inappropriate medications for older patients. (24th March 2020) - Rodrigues, D; Herdeiro, MT; Alcobia, A; Aperta, J; Morgado, M; Roque, F
Abstract : Background and importance: Some medicines are described as potentially inappropriate medications (PIM) for older patients. At least one PIM is regularly prescribed in 25–56% of hospitalised elderly patients, 1 and have been associated with adverse drug reactions in this population. Aim and objectives: To identify what medicines classified as PIM by three different tools are present in national hospital formulary of medicines (NHFM) and to check what information, if any, is in the summary of product characteristics (SmPC) about precautions in older patients. Material and methods: A search (September 2019) of the Portuguese NHFM, through the National Medicines and Health Products Authority (INFARMED) website, was made for all medicines included in the EU(7)-PIM list, in the STOPP V.2 criteria and in the 2019 Beers criteria. For each PIM found in the NHFM, the SmPC was analysed to check the recommendations made for older patients. Results: There are 242 chemical substances included in the Portuguese NHFM that were classified as PIM by at least one of the three tools. It was observed that, of these 242 chemical substances, 181 were classified as PIM by the STOPP criteria, 136 by the EU(7)-PIM list and 64 by Beers criteria. About 17% of identified PIMs were present in all three tools. About 27% of all PIM in the NHFM belonged to the ATC group C (cardiovascular system), 23% to group N (nervous system) and about 15% to group A (alimentary tract and metabolism). The SmPC of about 36% of the identified PIMs did not have special recommendations or precautions for use in older patients. Conclusion and relevance: Identification of PIM by hospital pharmacists, using adequate tools, is essential to contribute to the reduction in drug related problems in older patients. References and/or acknowledgements: 1. Scott, et al. Using EMR-enabled computerised decision support systems to reduce prescribing of potentially inappropriate medications: a narrative review. Ther Adv Neurol Disord 2017;23:153–156. Acknowledgements: This work was financially supported by the project APIMedOlder (PTDC/MED-FAR/31598/2017), funded by FEDER/FNR, POCI-01-0145-FEDER-031598, and by national funds (OE), through FCT/MCTES. No conflict of interest.